COMPARATIVE CHARACTERISTICS OF THE STRUCTURE OF THE VENOUS WALL OF THE EXTREMITIES OF HUMANS AND DOGS - Евсюков, Дмитрий Алексеевич; Цуканов, Антон Юрьевич; Цуканов, Юрий Тихонович; Дорофеева, Вера Павловна; Снитко, Илья Олегович; Аликберов, Мурат Ханапиевич; Кузовкин, Александр Николаевич; Винник, Илья Евгеньевич (Medicine in Kuzbass, 2024)
The study of the causes and mechanisms of development of varicose veins of the lower extremities does not lose its relevance. Most often, Wistar rats are used in experiments for morphological studies of the venous system of the lower extremities. However, modeling and studying varicose veins in dogs may be a more promising alternative. At the same time, no studies were found on the study of the normal morphology of the wall of the superficial veins in dogs.Objective. To study the morphological features of the structure of the medial saphenous vein of the dog and the great saphenous vein of the human.Materials and methods. A morphological study and comparison of the wall of the medial saphenous vein of 5 mongrel dogs and the great saphenous vein of 5 people who died at the age of 50 from various causes and did not have chronic venous diseases at the time of death were performed.Research results and discussion. The study identified the main morphological similarities and differences in the structure of the vein wall of dogs and humans. These architectural features determine hemodynamic processes in the venous bed of the lower extremities.Conclusion. The identified differences in the structure of the great saphenous vein of humans and the medial saphenous vein of dogs are probably due to the upright posture of the former and are an adaptive-compensatory mechanism for regulating venous tone. At the same time, the identified difference in structure cannot serve as a reason for refusing to interpolate data when modeling varicose veins in dogs in an experiment.
Keywords: phlebopathy; varicose veins; morphology; dogs